Study on supercritical CO2 extraction process, volatile components and antioxidant activity of rose oil from Dianhong rose - LIU Jin-yun; CHANG Jian; JIANG Zhuo-fang; XU Chong-jun; CHENG Wan; WU Heng (Shipin yu jixie)
Objective: Comprehensive utilization of Dianhong rose resources to improve the added value of products. Methods: The single-factor experiment and response surface experiment were used to optimize the extraction process of supercritical CO2 with essential oil yield as the measurement index. The composition and relative content of different rose oils were analyzed by GC-MS. The components and relative contents of different rose oils were analyzed by GC-MS, and the antioxidant activities of different rose oils were evaluated. Results: The results showed that the optimal extraction parameters were as followed: particle size of 40 mesh, extraction pressure of 25.5 MPa, extraction temperature of 45.5 ℃, extraction time of 123 min, CO2 flow rate of 20 L/h. Under these conditions, the essential oil yield of rose was 1.185%. A total of 74 compounds were identified from different Dianhong rose oil, and the total volatile substances of Anning Dianhong rose essential oil were the highest. The essential oil of Yunnan Dianhong rose had good ability to scavenge free radicals. The antioxidant activities of essential oil from different producing areas were obviously different. Conclusion: The essential oil extracted by supercritical CO2 has good quality and can be used as a natural antioxidant.